Modelling damage in nuclear graphite - Becker, T; Marrow, J (Chinese Society of Theoretical and Applied Mechanics, 2013)
In this paper a non-local coupled plasticity and damage model for nuclear graphite is presented. The model is the adaption of an existing model for quasi-brittle materials that allows for the degradation (as a function of load) of the material properties. The model arises from the continuum-based approach and uses concepts of isotropic damaged elasticity in combination with isotropic tensile and compressive plasticity to represent inelastic behaviour. In this work fracture of Gilsocarbon polygranular graphite is simulated in the FE environment for compact tension and three point bend specimens. The model consists of a combination of non-associated multi-hardening plasticity and scalar (isotropic) damage elasticity that describe the irreversible damage that occurs during the fracturing process in graphite. The simulations exhibit the observed softening and degradation of the material and found to be size and geometry independent.